Vincetoxicum xinpingense (Asclepiadeae, Asclepiadoideae, Apocynaceae), a new species from Yunnan Province, China - Jiang, Li-Qiong; Li, Yuan-Yuan; Zhu, Xin-Xin; Wang, Yue-Hua; Peng, Hua (Phytotaxa, 2018)
Vincetoxicum xinpingense, a new species from the Ailao Mountains in Yunnan Province, China, is described and illustrated. It is morphologically similar to V. sublanceolatum, Tylophora forrestii, and T. chingtungensis, but can be distinguished by several characters: shape and size of leaves, size of corolla lobes, length and shape of corona, attachment position of corona to the anthers, and orientation of pollinia. In addition, conservation status and other relevant notes are provided.